Penerapan Pembelajaran Kooperatif Tipe STAD Untuk Meningkatkan Pemahaman Konsep Rumus Keliling Dan Luas Persegi Panjang Pada Peserta Didik Di Kelas IV MIT Muhammadiyah Sukarame Bandar Lampung - Dwi Junia Lestari; Maryono (Gerasi Insan Nusantara, 2023)
Cooperative learning is learning carried out in groups. These groups are determined by educators with all existing considerations. There are several types of learning, one of which is STAD. STAD or Student Team Achievement Division is one of the oldest and most researched forms of cooperative learning. STAD type cooperative learning consists of five main components, namely: (1) team, (2) class presentation, (3) quiz, (4) individual progress score, and (5) team recognition. This research uses a type of classroom action research, where the necessary data is obtained from the implementation of the cycle. There are two cycles carried out by the author. Based on the implementation of this cycle, the author obtained the results that were the aim of this research. This research aims to improve conceptual understanding of the formula for the perimeter and area of ​​a rectangle in class IV students at MIT Muhammadiyah Sukarame. The results of this research prove that there is an increase in students' conceptual understanding of the formula for the perimeter and area of ​​a rectangle. These results can be seen from the cycles that have been implemented.